Quality Analysis of Hot Rolled Pickled and Oiled (HRPO) Products with Statistical Quality Control (SQC) And Failure Mode and Effect Analysis (FMEA) Methods (Case study: At PT Sun Rise Mill) - Fauzi Dwi Satrio; Sumiati Sumiati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
PT Sun Rise Mill is a company that is part of the SUNRISE GROUP domiciled in the Mojekerto area. PT Sun Rise Mill is a manufacturing company that has been established since 2018 which is engaged in the production of hot rolled pickle oil or HRPO rolled steel. PT Sun Rise Mill in every production there are still problems regarding defects that occur such as Under Pickle, Bad Trim, Protuding and Wavy Edge which affect the quality. The purpose of this study was to determine the presentation of the most dominant defects, the factors causing the defects, and the effects they caused, as well as to propose the appropriate improvements to improve the quality of hot rolled pickle oil rolled steel products. The methods used are Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA). SQC tools are check sheets, stratification, histograms, paretto diagrams, scatter diagrams, control charts, and cause and effect diagrams. Meanwhile, FMEA is used as a proposal to improve the results of the cause-and-effect diagram. Based on the results of research on SQC, the most dominant defects were Under Pickle (50.86%), after that Bad Trim (22.63%), Wavy Edge (18.76%), and Wavy Edge (7.73%). Based on the results of analysis and calculations on FMEA, it is known that the problem causing disability with the highest RPN value of 294 is the human factor with the cause of the operator being less careful in the washing steps when mixing HCL is not appropriate. Recommendations for improvements that can be made are by conducting periodic monitoring when mixing HCL.